2023
DOI: 10.1111/imr.13217
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific and cross‐reactive T cells in protection and disease

Abstract: Human T cells have a diverse T-cell receptor (TCR) repertoire that endows them with the ability to identify and defend against a broad spectrum of antigens. The universe of possible antigens that T cells may encounter, however, is even larger. To effectively surveil such a vast universe, the T-cell repertoire must adopt a high degree of crossreactivity. Likewise, antigen-specific and cross-reactive T-cell responses play pivotal roles in both protective and pathological immune responses in numerous diseases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 230 publications
0
9
0
Order By: Relevance
“…Cross‐reactive T cell responses play decisive roles in evaluating the appropriate vaccine target for protection against infection with viral variants 29 . To assess cross‐T cell responses among DNA vaccines, T cell responses to SARS‐CoV‐2 spike proteins from PS and different VOCs were measured in the splenocytes of vaccinated mice using murine IFN‐γ Elispot kits (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Cross‐reactive T cell responses play decisive roles in evaluating the appropriate vaccine target for protection against infection with viral variants 29 . To assess cross‐T cell responses among DNA vaccines, T cell responses to SARS‐CoV‐2 spike proteins from PS and different VOCs were measured in the splenocytes of vaccinated mice using murine IFN‐γ Elispot kits (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Identifying immunodominant T cell epitopes on myocarditic viruses and their homologous cardiac antigens could enable antigen‐specific immunotherapy to selectively tolerize those cross‐reactive T cells 110 . Determining susceptibilities like HLA associations may help personalize antigen‐specific prevention or treatment based on an individual's molecular mimicry risk 111 …”
Section: Autoimmune Myocarditismentioning
confidence: 99%
“…This deficit in TCR diversity is resolved by T cell cross-reactivity, that is the ability of a single TCR to bind multiple peptide-MHC complexes, albeit with different affinities. In addition to the theoretical need, numerous independent studies have experimentally demonstrated the existence of cross-reactive T cells [reviewed in ( 9 , 10 )].…”
mentioning
confidence: 99%